WOMEN’S HEALTH AND EDUCATION: KNOWLEDGE, PRACTICES, AND PUBLIC POLICIES - Aline Ferreira Brito Rodrigues, Beatriz; Teles Frazão, Cristiane; Monique Alves Desidério, Bárbara; Araújo Ferreira Passos , Letícia; Barbosa Santos, Larissa; Daminelle Lima Cavalcante, Brendha; Nelson Martins Júnior, Leonidas (Revista Gênero e Interdisciplinaridade, 2026)
This article aims to analyze the interrelationships between women’s health, educational practices, and public policies, based on a narrative review of academic productions published between 2022 and 2025. The research identified health education experiences aimed at different groups of women, considering markers such as territory, class, race, gender identity, and context of social vulnerability. The analysis of the texts allowed the construction of two thematic categories: (1) Health education as an emancipatory tool: women’s voices, bodies, and practices; and (2) Challenges and invisibilities in public health policies for women in vulnerable contexts. The results demonstrate that health education, when guided by dialogue, active listening, and the valuing of popular knowledge, contributes to strengthening women’s autonomy and protagonism. On the other hand, persistent limitations in public policies are evident, which still reproduce models centered on motherhood and neglect the diversities of gender, race, and territory. It is concluded that the effective implementation of comprehensive women’s health care depends on the articulation between transformative educational actions, inclusive policies, and practices committed to equity and social justice.